Practical Recommendations Relevant to the Use of Resistance Training for COVID-19 Survivors - Gentil, Paulo; de Lira, Claudio Andre Barbosa; Coswig, Victor; Barroso, Weimar Kunz Sebba; Vitorino, Priscila Valverde de Oliveira; Ramirez-Campillo, Rodrigo; Martins, Wagner; Souza, Daniel (Frontiers in Physiology, 2021)
The novel coronavirus disease (COVID-19) has emerged on the end of 2019 and caused a global pandemic. Although COVID-19 predominantly affects the respiratory system, evidence indicates that it is a multisystem disease with a special impact on the cardiovascular system. Although the long-term consequences of COVID-19 are not well-known, evidence from similar diseases alerts for the possibility of long term impaired physical function and reduced quality of life, especially in those requiring critical care. Therefore, rehabilitation strategies are needed to improve outcomes in COVID-19 survivors. Among the possible strategies, resistance training (RT) might be particularly interesting, since it has been shown to increase functional capacity both in acute and chronic respiratory conditions as well as in cardiac patients. The present article aims to propose evidence-based and practical suggestions for RT prescription for people that have been diagnosed with COVID-19 with a special focus on immune, respiratory, and cardiovascular systems. Based on the current literature, we present RT as a possible safe and feasible activity that can be time-efficient and easy to be implemented in different settings.